The therapeutic Role of Medicinal Plants in Treating Corona Epidemic Disease (Eucalyptus as Applied Study) - Samira Mohammed Salih Al-Samaraee; Afak Ibrahem Jumah (Indian Journal of Forensic Medicine & Toxicology, 2021)
The study was conducted to know the effect of treatment with the hot aqueous extract of the green leaves ofEucalyptus camldulensis on the initial symptoms associated with Coronavirus disease. Three concentrationsof the hot aqueous extract were used, which are (0,25,50 g.L-1) boiled distilled water, and the results in kindshowed the infected volunteer patients the following: The results showed that there was an effective andsignificant increase in the use of the hot aqueous extract by the volunteer patients at a concentration of 50 gof green eucalyptus leaves per liter of water only. The percentage of those recovering from the symptoms ofthe disease was 63% when they inhaled the water vapour of the leaves for a period of 15-30 seconds, oncea day for the age group (25-45) years, while the percentage of recovery for patients from the group (45-65)years was 55%. The results recorded a recovery percentage of 48.1% for infected patients and volunteers,and for the age group of 25-45 years, from the initial symptoms associated with the Coronavirus, such asfever, coughing and shortness of breath, and a recovery percentage of 29.6% and for the older age groupfrom 45 to 65 years, when they inhale the steam of boiling water of the leaves of the extract for a period of15-30 seconds and only once a day